Anti‐C1 domain antibodies that accelerate factor VIII clearance contribute to antibody pathogenicity in a murine hemophilia A model. (13th August 2018) - Batsuli, G.; Ito, J.; Mercer, R.; Baldwin, W. H.; Cox, C.; Parker, E. T.; Healey, J. F.; Lollar, P.; Meeks, S. L.
Abstract : Essentials Inhibitor formation remains a challenging complication of hemophilia A care. The Bethesda assay is the primary method used for determining bleeding risk and management. Antibodies that block factor VIII binding to von Willebrand factor can increase FVIII clearance. Antibodies that increase clearance contribute to antibody pathogenicity. Summary: Background: The development of neutralizing anti‐factor VIII (FVIII) antibodies remains a challenging complication of modern hemophilia A care. In vitro assays are the primary method used for quantifying inhibitor titers, predicting bleeding risk, and determining bleeding management. However, other mechanisms of inhibition are not accounted for in these assays, which may result in discrepancies between the inhibitor titer and clinical bleeding symptoms. Objectives: To evaluate FVIII clearance in vivo as a potential mechanism for antibody pathogenicity and to determine whether increased FVIII dosing regimens correct the associated bleeding phenotype. Methods: FVIII −/− or FVIII −/− /von Willebrand factor (VWF) −/− mice were infused with anti‐FVIII mAbs directed against the FVIII C1, C2 or A2 domains, followed by infusion of FVIII. Blood loss via the tail snip bleeding model, FVIII activity and FVIII antigen levels were subsequently measured. Results: Pathogenic anti‐C1 mAbs that compete with VWF for FVIII binding increased the clearance of FVIII–mAb complexes in FVIII −/− mice but not in FVIII −/− /VWF −/− mice. Additionally, pathogenic anti‐C2 mAbs that inhibit FVIII binding to VWF increased FVIII clearance in FVIII −/− mice. Anti‐C1, anti‐C2 and anti‐A2 mAbs that do not inhibit VWF binding did not accelerate FVIII clearance. Infusion of increased doses of FVIII in the presence of anti‐C1 mAbs partially corrected blood loss in FVIII −/− mice. Conclusions: A subset of antibodies that inhibit VWF binding to FVIII increase the clearance of FVIII–mAb complexes, which contributes to antibody pathogenicity. This may explain differences in the bleeding phenotype observed despite factor replacement in some patients with hemophilia A and low‐titer inhibitors.